Crosstalk between Wnt/β-catenin and Hedgehog/Gli signaling pathways in colon cancer and implications for therapy - Song, Li (Cancer Biol Ther, 2015)
Wnt/β-catenin and Hedgehog/Gli signalings play key roles in multiple biogenesis such as embryonic development and tissue homeostasis. Dysregulations of these 2 pathways are frequently found in most cancers, particularly in colon cancer. Their crosstalk has been increasingly appreciated as an important mechanism in regulating colon cancer progression. Our studies into the link between Wnt/β-catenin and Hedgehog/Gli signalings in colon cancer revealed several possible crosstalk points and suggested potential therapeutic strategies for colon cancer.